NIR surface enhanced Raman spectra of biological hemes: Solvation and plasmonic metal effects. (19th July 2021) - Ingraham, Harrison M.; Premasiri, W. Ranjith; Ziegler, Lawrence D.
Abstract: Surface enhanced Raman spectra (SERS) excited at 785 nm are reported for hemoglobin, myoglobin, two heme B proteins, and cytochrome c, a heme C protein, solubilized in a variety of solvent systems and then placed on Au and Ag substrates. These solvent environments include H2 O pH 7.4, HCl/water pH 2, HCl/50% ethanol pH 2, 50% acetic acid and the organic layer of a pH 2 HCl/butanone mixture. To obtain the most intense SERS spectra of heme B proteins (Mb and Hb) it is not sufficient to be in a low pH (pH ~ 2) denaturing environment. A hydrophobic solvent component is additionally required in order to efficiently solubilize the cleaved heme moiety and consequently observe intense SERS spectra indicative of these heme B proteins. Although both heme B proteins exhibit virtually identical, metal (Au, Ag) specific SERS spectra, Cyt c is much weaker in the low pH environments and only displays a Ag‐like SERS spectrum on both metals indicating that this heme C protein is not cleaved in any of these solvation environments. The strong SERS signals of hemoglobin and myoglobin are due to hemin and ferric acetate heme formed in pH 2 HCl/ethanol and pH 2/50% acetic acid solutions respectively. SERS vibrational features confirm oxidation state, coordination number and ligands. SERS signals due to globin protein aggregation effects are reduced in low pH solvent systems with polarities lower than pure water. These results confirm the mechanism of a successful acetic acid protocol previously developed for the highly sensitive SERS detection of dried blood for forensic applications and indicate how it may be further improved to achieve even higher SERS sensitivity for heme protein detection. Abstract :